Comment on "synthesis and structural properties of vanadium doped zinc oxide" by R. Abaira, E. Buffagni, A. Matoussi, H. Khmakhem, C. Ferrari, and published in Superlattices and Microstructures 86 (2015) 438–445. (November 2018) - Tomaszewski, Paweł E.
Highlights: Several errors were found and corrected. The preferred orientation is not present in the studied samples. Some not correct statements were explained. Lattice parameters are given with incredible high accuracy. All corrections concern the crystallographic part of paper.